Aligning Medication Reconciliation and Secure Messaging: Qualitative Study of Primary Care Providers' Perspectives - Heyworth, Leonie; Clark, Justice; Marcello, Thomas B; Paquin, Allison M; Stewart, Max; Archambeault, Cliona; Simon, Steven R (JMIR Publications, 2013)
BackgroundVirtual (non-face-to-face) medication reconciliation strategies may reduce adverse drug events (ADEs) among vulnerable ambulatory patients. Understanding provider perspectives on the use of technology for medication reconciliation can inform the design of patient-centered solutions to improve ambulatory medication safety. ObjectiveThe aim of the study was to describe primary care providers' experiences of ambulatory medication reconciliation and secure messaging (secure email between patients and providers), and to elicit perceptions of a virtual medication reconciliation system using secure messaging (SM). MethodsThis was a qualitative study using semi-structured interviews. From January 2012 to May 2012, we conducted structured observations of primary care clinical activities and interviewed 15 primary care providers within a Veterans Affairs Healthcare System in Boston, Massachusetts (USA). We carried out content analysis informed by the grounded theory. ResultsOf the 15 participating providers, 12 were female and 11 saw 10 or fewer patients in a typical workday. Experiences and perceptions elicited from providers during in-depth interviews were organized into 12 overarching themes: 4 themes for experiences with medication reconciliation, 3 themes for perceptions on how to improve ambulatory medication reconciliation, and 5 themes for experiences with SM. Providers generally recognized medication reconciliation as a valuable component of primary care delivery and all agreed that medication reconciliation following hospital discharge is a key priority. Most providers favored delegating the responsibility for medication reconciliation to another member of the staff, such as a nurse or a pharmacist. The 4 themes related to ambulatory medication reconciliation were (1) the approach to complex patients, (2) the effectiveness of medication reconciliation in preventing ADEs, (3) challenges to completing medication reconciliation, and (4) medication reconciliation during transitions of care. Specifically, providers emphasized the importance of medication reconciliation at the post-hospital visit. Providers indicated that assistance from a caregiver (eg, a family member) for medication reconciliation was helpful for complex or elderly patients and that patients' social or cognitive factors often made medication reconciliation challenging. Regarding providers' use of SM, about half reported using SM frequently, but all felt that it improved their clinical workflow and nearly all providers were enthusiastic about a virtual medication reconciliation system, such as one using SM. All providers thought that such a system could reduce ADEs. ConclusionsAlthough providers recognize the importance and value of ambulatory medication reconciliation, various factors make it difficult to execute this task effectively, particularly among complex or elderly patients and patients with complicated social circumstances. Many providers favor enlisting the support of pharmacists or nurses to perform medication reconciliation in the outpatient setting. In general, providers are enthusiastic about the prospect of using secure messaging for medication reconciliation, particularly during transitions of care, and believe a system of virtual medication reconciliation could reduce ADEs.